Educational partnership working: a case study in social capital - O'Brien, Stephen Martin (2015)
Collaborative partnership working would appear to be highly valued by Higher Education Institutions (HEI). This thesis is about one such educational partnership. The context is that of partnership working between Schools of Nursing located within Higher Education institutions and the National Health Service (NHS) to deliver the practice learning elements of the nursing curriculum. Such partnership arrangements are historically quite young and are thus worthy of investigation. There have been many iterations of the nursing curriculum but the central tenet that delivery is based on a partnership remains. The aim was to explore the experience of both academic and practice staff engaged in a partnership between one School of Nursing and an NHS partner. The following questions were posed. How does such a partnership manifest itself? What are the structural relationships? What are the motivating factors for participants? What capabilities are required to work in this way? What are the benefits and risks for participants and organizations? What determines a successful partnership? The literature yielded perspectives on both the concept and the operation of partnerships in the public sector. A case study of one partnership was undertaken. Data were collected through a qualitative research process underpinned by social phenomenology, which included documentary analysis and semi structured interviews with staff from the the HEI and NHS. Data were analysed using a framework based on the work of Hycner (1999). A theoretical framework of social capital influenced the analysis. Findings were largely supportive of the existing literature. The strongest elements of partnership related to partnership as a means of production, the importance of structured activity, equality, ambiguity of benefits, organizational advantage, leadership and professional imperatives. Furthermore the following aspects of social capital were seen as relevant to the discussion; trustworthiness, information, obligations, norms, networks and formal and informal relationships. The results add to nurse educators understanding of these partnerships. A set of “lessons learned” was constructed and areas for future research identified.